DOI: 10.31274/rtd-180817-3484
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the energy value of feed ingredients for young swine

Abstract: This material was produced from a microfilm copy of the original document. While the most advanced technological means to photograph and reproduce this document have been used, the quality is heavily dependent upon the quality of the original submitted. The following explanation of techniques is provided to help you understand markings or patterns which may appear on this reproduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Taking the value of 0.95 as the conversion coefficient of digestible energy into ME (Diggs et al 1965;De Goey, 1973), the mean coefficient for the apparent digestibility of gross energy in the present experiments was 0.85, which is in agreement with results previously obtained with the same diet (Le Dividich et al 1977). Entringer .et al (1975) reported detrimental effects of diarrhoea on the apparent digestibility of N in growing pigs.…”
Section: Growth Performance and Energy Metabolizabilitysupporting
confidence: 92%
“…Taking the value of 0.95 as the conversion coefficient of digestible energy into ME (Diggs et al 1965;De Goey, 1973), the mean coefficient for the apparent digestibility of gross energy in the present experiments was 0.85, which is in agreement with results previously obtained with the same diet (Le Dividich et al 1977). Entringer .et al (1975) reported detrimental effects of diarrhoea on the apparent digestibility of N in growing pigs.…”
Section: Growth Performance and Energy Metabolizabilitysupporting
confidence: 92%
“…The soluble fraction of NSPs enhances the digesta viscosity by directly binding the water molecules at low concentrations or by interacting themselves to form a network as the concentration increases [233]. Water-holding capacity is another characteristic of NSPs that may influence the antinutritional properties of NSPs [234]. The ability to absorb large amounts of water and maintain normal motility of the gut becomes an important attribute of insoluble NSPs in poultry nutrition [235].…”
Section: Non-starch Polysaccharidesmentioning
confidence: 99%
“…The increase in gut viscosity lowers the mixing of digestive enzymes and substrates in the intestinal lumen [230]. Combined with increased mucus production, NSPs can also increase the resistance of the unstirred water layer at the intestinal surface [234]. Furthermore, NSPs in cell walls physically inhibit the access of digestive enzymes to nutrients that are encapsulated within cell walls.…”
Section: Non-starch Polysaccharidesmentioning
confidence: 99%
“…Calculated digestibility values, then, should be referred to as "apparent." For AAs and fat, endogenous losses are quite substantial and are influenced by the presence of other nutrients as well as nonnutrients in the diet (70). Nyachoti et al (71) concluded that endogenous nutrient losses interfere with the additivity of nutrient digestibilities in mixtures of ingredients present in complete foods, and with metabolic losses associated with the use of absorbed nutrients for production.…”
Section: In Vivo Nutrient Digestibilitymentioning
confidence: 99%